CRM - zintegrowany system wspomagający kształtowanie relacji z klientami przez banki spółdzielcze - Rudawska, Edyta (CRM - an Integrated System Facilitating the Process of Creating Long-Term Relationships with Customers by Co-Operative Banks, 2005)
Changes that took place on a co-operative banks market as a consequence of the consolidation process have improved their economic situation. That fact and a local scale of activity, as well as close and often informal contacts with customers make those banks perform an increased value for Polish society. To keep and enhance that position banks should focus on fulfilling increasing customers needs in order to acquire their loyalty. Those activities will be much easier and more effective thanks to the use of new technology which facilitates the process of building long-term relations. One of such technologies is Customer Relationship Management - CRM. The aim of the article is to show the concept of CRM as an integrated system and its role in the process of creating relationships with customers by co-operative banks
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 123-131